Effect of Psychoneural Factors on Intestinal Epithelial Function - M Cecilia Berin; Mary H Perdue (Canadian Journal of Gastroenterology)
Stress has been associated with abnormal gastrointestinal function, including diarrhea and abdominal pain, and stress-associated gastric ulceration has frequently been documented. Stress can also exacerbate ongoing pathophysiology and often precedes relapses in patients with inflammatory bowel disease or irritable bowel syndrome. The relatively new field of psychoneuroimmunology is involved with the elucidation of mechanisms that explain the link between the central nervous system and immune-mediated pathophysiology. Recent progress examining the interaction among the nervous system, the immune system and the epithelium of the intestine is discussed, and the evidence for central nervous sysytem control of this interaction is examined.